2019
DOI: 10.1111/1753-0407.12938
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of brown adipose tissue activation in diabetic mice

Abstract: BackgroundBrown adipose tissue (BAT) has been regarded as a potential target organ to combat obesity and related metabolic disorders. However, the effect of BAT activation on the development of diabetic kidney disease (DKD) remains unclear.MethodsDiabetic mice were induced by streptozotocin (STZ) combined with a high‐fat diet. To activate BAT, mice were administered 1 mg/kg per day, i.p., CL316,243, a β3‐adrenergic receptor agonist, for 4 weeks. Blood glucose, serum lipids, adipokines, 24‐hour urinary albumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Our previous study had also shown that activation of brown adipose tissue could significantly up-regulate the levels of serum miR-99a, miR-99b, miR-30b, miR-100, etc. [43]. Study by Thomou et al has shown that adipose tissue was the main source of circulating miRNAs and that the level of miR-99a and miR-99b in the circulation was significantly increased after BAT transplantation in a fat-specific knockout of the miRNA-processing enzyme Dicer mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study had also shown that activation of brown adipose tissue could significantly up-regulate the levels of serum miR-99a, miR-99b, miR-30b, miR-100, etc. [43]. Study by Thomou et al has shown that adipose tissue was the main source of circulating miRNAs and that the level of miR-99a and miR-99b in the circulation was significantly increased after BAT transplantation in a fat-specific knockout of the miRNA-processing enzyme Dicer mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the AMPK‐SIRT1‐PGC1α‐axis after the binding of APN to Adipo‐R1 inhibits NF‐κB and its downstream pathway, thereby significantly reducing the 24 hours urinary albumin level, preventing inflammation and oxidative stress, inhibiting the accumulation of renal ECM and ameliorating renal morphological abnormalities. This delays the progression of renal fibrosis in experimental animals 17 . In addition, study of a model of contrast‐induced nephropathy in Sprague‐Dawley rats reported that AdipoRon protected against contrast‐induced nephropathy via activation of the AMPK pathway, and also significantly reversed the pathological effects of contrast on serum creatinine, blood urea nitrogen and creatinine clearance level 18 …”
Section: Role Of Apn In Renal Fibrosismentioning
confidence: 99%
“…155 Therefore, over-whelming evidence shows that AMPK/ SIRT1 activation reduces renal inflammation, oxidative stress and podocyte apoptosis in DN patients, thus protecting against kidney damages. 156,157 AMPK and SIRT1 are downstream kinases for FGF21. Activation of AMPK stimulates glucose metabolism and oxidation of fatty acids in patients with diabetes mellitus.…”
Section: Fgf and The Pi3k/akt Signaling Pathwaymentioning
confidence: 99%